Pembunuhan sebagai Upaya Pembelaan Diri dalam Pandangan Hukum Islam dan Hukum Positif : Murder as an Effort in Self-Defense in the View of Islamic Law and Positive Law - Abdullah Sandi; Kasman Bakry; Jamaluddin, Jamaluddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to analyze the concept of murder as an effort in self-defense from the perspective of Islamic law and Indonesian positive law, with special emphasis on Article 34 of Law Number 1 of 2023. This research uses normative juridical methods with a comparative approach to explore the similarities and differences in self-defense arrangements between Islamic law and Indonesian positive law. The research results show that although there are differences in perspective and emphasis, both legal systems recognize the importance of the right to self-defense and the principle of proportionality in such actions. A thorough understanding of these two perspectives is essential to ensure fair and balanced law enforcement in Indonesia. The research also found that in the context of Islamic law, self-defense is governed by strict principles that take into account the perpetrator's intentions and spiritual state. According to relevant verses of the Koran and hadith, self-defense in emergency situations is permissible and must be carried out in reasonable limits. The right to self-defense is also recognized by Indonesian positive law, especially Article 34 of Law no. 1 of 2023 and Article 49 of the Criminal Code. To ensure that self-defense actions are carried out proportionally and not excessively, positive law emphasizes objective evidence and concrete circumstances at the time of the incident. This study found that, although these two legal systems share the same recognition of the right to self-defense, they use different approaches and emphases to do so.